Impaired ketogenesis is associated with metabolic-associated fatty liver disease in subjects with type 2 diabetes - Lee, Sejeong; Bae, Jaehyun; Jo, Doo Ri; Lee, Minyoung; Lee, Yong-ho; Kang, Eun Seok; Cha, Bong-Soo; Lee, Byung-Wan (Frontiers in Endocrinology, 2023)
Aims: The ketogenic pathway is an effective mechanism by which the liver disposes of fatty acids (FAs) to the peripheral tissues. Impaired ketogenesis is presumed to be related to the pathogenesis of metabolic-associated fatty liver disease (MAFLD), but the results of previous studies have been controversial. Therefore, we investigated the association between ketogenic capacity and MAFLD in subjects with type 2 diabetes (T2D). Methods: A total of 435 subjects with newly diagnosed T2D was recruited for the study. They were classified into two groups based on median serum β-hydroxybutyrate (β-HB) level: intact vs. impaired ketogenesis groups. The associations of baseline serum β-HB and MAFLD indices of hepatic steatosis index, NAFLD liver fat score (NLFS), Framingham Steatosis index (FSI), Zhejian University index, and Chinese NAFLD score were investigated. Results: Compared to the impaired ketogenesis group, the intact ketogenesis group showed better insulin sensitivity, lower serum triglyceride level, and higher low-density lipoprotein-cholesterol and glycated hemoglobin levels. Serum levels of liver enzymes were not different between the two groups. Of the hepatic steatosis indices, NLFS (0.8 vs. 0.9, p=0.045) and FSI (39.4 vs. 47.0: p=0.041) were significantly lower in the intact ketogenesis group. Moreover, intact ketogenesis was significantly associated with lower risk of MAFLD as calculated by FSI after adjusting for potential confounders (adjusted odds ratio 0.48, 95% confidence interval 0.25-0.91, p=0.025). Conclusions: Our study suggests that intact ketogenesis might be associated with decreased risk of MAFLD in T2D.